DIFFERENT ANALYTICAL TECHNIQUES FOR THE ANALYSIS OF ANTICANCER DRUGS-BOSUTINIB, ENCORAFENIB AND DABRAFENIB-A REVIEW - JAYAPRAKASH, RAMESH; VENKATESAN, ANITHA; VENGADHAJALAPHATHI, PRIYADHARSHINI; RAMA, DIVYA; SETTU, ARCHANA (International Journal of Current Pharmaceutical Research, 2023)
In this present situation there is an increase in the number of diseases has been observed but before this drug come to market, it must undergo several procedures. The validation and analytical methods are the important techniques that help in ensuring its purity and reliability. This process involves the use of various analytical techniques to collect data about the drug. This review includes various types of analytical techniques such as ultraviolet-visible Spectrophotometric and chromatography methods such as high-performance liquid chromatography, hyphenation techniques such as LC-MS for the estimation of selected anti-cancer drugs.